4H-SiC P+N UV Photodiodes: Influence of Temperature and Irradiation. Issue 1693 (10th June 2014) - Bérenguier, B.; Ottaviani, L.; Biondo, S.; Palais, O.; Lazar, M.; Milesi, F.; Torregrosa, F.; Kalinina, E.; Lebedev, A.; Vervisch, W.; Lyoussi, A.
ABSTRACT: 4H-SiC p+n photodiodes based on ultrathin-junctions have been fabricated with distinct processes for the p+-region creation: either with Aluminium conventional ion implantation, or with Boron Plasma Ion Immersion Implantation. Spectral sensitivity measurements were performed at several temperatures from room temperature up to 340°C, with incident wavelengths ranging from 200 to 400 nm. Both responses are characterized by a stability between 200 and 270 nm, and a important increase with temperature between 270 and 380 nm. This fact has to be related to the two different kinds of optical absorption phenomena in SiC with respect to the wavelength, which are direct and indirect (phonon assisted) transitions. When decreasing the temperature, we noticed a hysteresis effect, which could be due to charge trapping by temperature activated defects. After strong proton and electron irradiations, the diodes showed a stability of the response below 270 nm, making them suitable for use in harsh environments. Simulation was performed at room temperature, with a good correlation between simulated and experimental room temperature curves.